Photoreduction of CO2 to CO by a mononuclear Re(i) complex and DFT evaluation of the photocatalytic mechanism. Issue 51 (5th June 2015) - Shakeri, Jamaladin; Farrokhpour, Hossein; Hadadzadeh, Hassan; Joshaghani, Mohammad
<x xml:space="preserve">Abstract</x> A new method for the preparation of fac-[Re(phen-dione)(CO)3Cl] and its application for the photochemical reduction of CO2 to CO have been reported.